2021
DOI: 10.1108/jsbed-11-2020-0420
|View full text |Cite
|
Sign up to set email alerts
|

Which resource acquisition acts drive growth of informal firms? Evidence from Zambia

Abstract: PurposeThe study seeks to differentiate informal firms with high-growth prospects by their resource acquisition acts and to improve identification of growth-oriented informal firms for effective design and targeting of support measures.Design/methodology/approachAn original set of firm-level data was collected using face-to-face survey in Lusaka, Zambia. Six clearly defined criteria were used to sample informal firms, apart from general informal business. Regression analyses were conducted to test the associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 85 publications
0
12
0
Order By: Relevance
“…Such interaction enhanced relationships and led to building trust – reflecting work by Berrou and Combarnous’s (2012) regarding trade ties and mutual aid between entrepreneurs. Similarly, Kebede (2020) reports that increased networking activity is associated with higher output among informal entrepreneurs with smaller enterprises and poor access to formal institutions, whilst Tang and Konde (2021) established that networking with formal businesses increased the earnings of informal firms. Meanwhile, we found that trust, faithfulness and loyalty influenced referral decisions from established customers to informal entrepreneurs, This confirms evidence by Amoako and Lyon (2014), Amoako and Matlay (2015) that trust amongst Ghanaian small exporters is tied to both parties having a link to a familiar person, established long-standing trading relationships, and being a member of the same network.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Such interaction enhanced relationships and led to building trust – reflecting work by Berrou and Combarnous’s (2012) regarding trade ties and mutual aid between entrepreneurs. Similarly, Kebede (2020) reports that increased networking activity is associated with higher output among informal entrepreneurs with smaller enterprises and poor access to formal institutions, whilst Tang and Konde (2021) established that networking with formal businesses increased the earnings of informal firms. Meanwhile, we found that trust, faithfulness and loyalty influenced referral decisions from established customers to informal entrepreneurs, This confirms evidence by Amoako and Lyon (2014), Amoako and Matlay (2015) that trust amongst Ghanaian small exporters is tied to both parties having a link to a familiar person, established long-standing trading relationships, and being a member of the same network.…”
Section: Discussionmentioning
confidence: 99%
“…In line with Omenma and Omeje (in press), the use of ICTs is seen to be a common practice among informal entrepreneurs. Similarly, Tang and Konde (2021) found that informal growth in business earnings is influenced by acquiring information and knowledge via online sources. The use of social media and relevant marketing skills allowed informal firms to reach customers at much lower costs and expand their visibility in the business landscape.…”
Section: Findings and Analysismentioning
confidence: 98%
See 3 more Smart Citations